The Role of Digitalization of Human Capital Strategies in Developing Employee Quality at PT. Tuah Turangga Agung - Qohar, Muhammad Fikri Bivani Al; Bagus, Ujang; Andriani, Aulia; Hermawan, Fachrezi Rizki; Baidawih, Muhammad Hafidz; Pratama, Muhammad Yoga; Wulani, Revi Dwi; Rahma, Rana Ardila (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The digitalization of human capital strategies has become a crucial element in enhancing employee quality in the current digital era. In an increasingly interconnected and dynamic business environment, companies need to adopt innovative approaches to strengthen and optimize their human resources. Human capital comprises a combination of knowledge, skills, innovation, and individual capabilities to create value in achieving specific goals. However, the quality of employees at PT. Tuah Turangga Agung, especially in terms of digitalization, still needs improvement. Employee development plans related to digitalization have not been fully realized. This research aims to explore the role of digitalized human capital strategies in enhancing employee quality at the company. Through the application of information and communication technology, companies can improve efficiency in human resource management. Digital innovation and automation enable companies to recruit, identify potential talents, and track employee progress more effectively. This study employs descriptive qualitative and quantitative methods to depict the impact of digitalized human capital strategies on employee quality development. The results indicate a significant and positive effect, urging companies to invest in digital solutions to enhance their workforce quality.